Legal and Ethical Dimensions of Computerized Cognitive Therapy for Neurodevelopmental Disorders in Children - Priyanka Kacker (Global Journal of Law, AI & Ethics, 2025)
The increasing use of computerized cognitive therapy tools—such as Brain Function Therapy and neurofeedback—in pediatric settings demands careful consideration of not only their clinical effectiveness but also the ethical and legal ramifications. These adaptive, non-invasive interventions promise to support children with neurodevelopmental issues like attention-deficit/hyperactivity disorder, autism spectrum conditions, and learning challenges. However, they pose challenges to existing norms around informed consent, privacy of neural data, and oversight. This paper examines how these technologies operate, evaluates evidence of their therapeutic impact, and explores the evolving legal and bioethical dialogue, including reforms like the recognition of brainwave data as sensitive in consumer privacy law and growing discourse around mental privacy and cognitive autonomy. Careful interdisciplinary governance is essential to ensure that cognitive neurotechnologies are integrated responsibly into clinical and educational practices.